Kesiapan Penerapan Zona Integritas Di Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo - Marhawati, Besse; Arwildayanto, Arwildayanto; Umar, Sahruni; Mas, Siti Roskina; Arifin, Arifin (Universitas Negeri Malang, 2023)
Abstract: This study aims to determine the readiness to implement the Zone of Integrity (ZI) in the Faculty of Education, Universitas Negeri Gorontalo, regarding change management, governance arrangements, and HR management. This study used a quantitative approach and the type of descriptive, explanatory research. Questionnaires, interviews, and document studies were conducted to obtain the data. Further, the data was analyzed using a simple descriptive technique expressed in the percentage formulation. The results showed that: (1) Readiness of ZI implementation in Faculty of Education in terms of change management was in the ready category, (2) Readiness of ZI implementation in Faculty of Education in terms of management arrangement was in the ready category, and (3) Readiness of ZI implementation in Faculty of Education in terms of HR management is in the ready category.Keywords: Integrity Zone Readiness; Implementation; Faculty of EducationAbstrak: Penelitian ini bertujuan untuk mengetahui kesiapan penerapan Zona Integritas di Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo ditinjau dari manajemen perubahan, penataan tata laksana, dan manajemen SDM. Penelitian menggunakan pendekatan kuantitatif dengan jenis deskriptif eksplanatori. Teknik pengumpulan data menggunakan kuesioner (angket), wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah teknik analisis deskriptif dengan menggunakan formulasi persentase. Hasil penelitian menunjukkan bahwa: (1) Kesiapan penerapan ZI di FIP ditinjau dari manajemen perubahan berada pada kategori siap, (2) Kesiapan penerapan ZI di FIP ditinjau dari penataan tata laksana berada pada kategori siap, dan (3) Kesiapan penerapan ZI di FIP ditinjau dari manajemen SDM berada pada kategori siap.Kata Kunci: Kesiapan Zona Integritas; Implementasi; Fakultas Ilmu Pendidikan